Comparison of PO and INC MPPT Methods Using FPGA In-The-Loop under Different Radiation Conditions - Çelikel, Reşat; Gundogdu, Ahmet (My University, 2021)
In photovoltaic (PV) systems, the Maximum Power Point Tracking (MPPT) algorithms are applied to obtain maximum efficiency under different atmospheric conditions. Among the MPPT methods, Perturb & Observe (PO) and Incremental Conductance (INC) methods are the oldest algorithms that have been used. Field Programmable Gate Arrays (FPGA) are used especially in applications requiring high speed. FPGA in-the-loop feature is used to test algorithms designed in MATLAB/Simulink environment. In this study, PO and INC methods were designed to work in FPGA environment. Both algorithms were tested under different radiation conditions by using FPGA-in-the-loop feature. The FPGA in-the-loop simulation result of PO and INC methods was shown graphically. Altera DE2-115 development board was used to test PO and INC MPPT algorithms. In addition, PO and INC methods were synthesized using the Quartus-II program. Comparisons of the simplicity of the algorithms were made based on the synthesis results. Thus, by using the FGPA in-the-loop feature and performing the synthesis process, both of the algorithms were tested and the areas covered by the algorithms in the FPGA were compared.
Keywords: Mühendislik; Elektrik ve Elektronik